Changes in Neutrophil to Lymphocyte Ratio, Lymphocyte to Monocyte Ratio, and Platelet to Lymphocyte Ratio During Palliative Radiotherapy May Predict Efficacy of Immune Checkpoint Inhibitor as Re-Challenge Treatment in Advanced Gastric Cancer: A Case Report - Chen, Jianxin; Wu, Xilin; Zhu, Shijian; Wang, Junhui (Frontiers in Oncology, 2022)
Introduction: Immunotherapy with programmed death-1 (PD-1) inhibitors, have been emerged as front line options in patients with advanced or metastatic gastric cancer. However, there were still two thirds patients who received PD-1 inhibitors treatment resulted in disease progression in one year. Subsequent treatment strategies as salvage options always lead to limited efficacy. Case description: Herein, we presented a case of recurrent metastatic gastric adenocarcinoma, had progressed on first line treatment with nivolumab, whose systematic inflammation parameters with neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), and platelet to lymphocyte ratio (PLR) were significantly changed by palliative radiotherapy on metastatic lymph nodes, has achieved persistent response to the re-challenge of immune checkpoint inhibitor, resulted with survival time reached fifty two months, and still in extension. Conclusions: We supposed that the palliative radiotherapy may lead to the correction of NLR, LMR, and PLR, and finally contributed to the efficacy of the re-challenge treatment by PD-1 inhibitor.